Telework, perception and family partnership. The Spanish situation after Covid-19 - Covadonga Gijón; Aurora Ruíz-Rúa; Fernando Fernández-Bonilla (International Telecommunications Society (ITS), 2023)
Before and after the pandemic COVID-19 and with the expansion of high-speed internet during the recent decades, a growing number of people are working from home, teleworking. Yet there is no consensus on how working from home affects workers' satisfaction in the literature. Using data from 2020 and 2021 this paper examines the satisfaction of those people who are more or less hostile to teleworking. Apart from the general positive perception of telework and the contribution it has made to work-life balance, time management and the reduction of commuting, there are also many who feel lonelier than before and there is a perception that it is more difficult to disconnect from work while working from home. Although the positive not be ignored, teleworking seems does not favour the better educated or the self-employed, who have lower levels of satisfaction in relation to the other variables. In fact, the self-employed are less satisfied overall. Therefore, companies and the public sector must make every effort to enhance these synergies, support training programmes and ensure work-life balance for teleworkers. Further lines of research should be taken into account in order to obtain a more clear and multydisciplinary analysis of telework.
Keywords: 330; Working at home; Telework; Consumers; Survey data; Econometric models